Investigating the nexus between fuel ethanol and CO2 emissions. A panel smooth transition regression approach - Cepoi, Cosmin-Octavian; Bran, Mariana; Dinu, Mihai (Journal of Business Economics and Management, 2020)
In this paper, we fill the gap in the literature by identifying a negative relationship between fuel ethanol consumption and CO2 emissions, building on a sample of 17 European countries covering seven years, from 2010 to 2016. Based on a Panel Smooth Transition Regression approach we show that countries with high levels of income inequality have difficulties in avoiding environmental degradation by promoting policies and regulations for more intense use of biofuels. Furthermore, we bring strong empirical evidence suggesting that biofuels could be an alternative in the future to reducing CO2 emissions. In our opinion, this non-linear analysis could provide the scientific basis for authorities, especially the European Commission to promote environmental policies to a specific country with different levels of carbon emissions rather than to the entire group.